2007
DOI: 10.1097/md.0b013e3181573059
|View full text |Cite
|
Sign up to set email alerts
|

Angioimmunoblastic T-Cell Lymphoma

Abstract: We retrospectively analyzed 77 patients with pathologically diagnosed angioimmunoblastic T-cell lymphoma from a single city. There were 43 men and 34 women; the median age was 64.5 years (range, 30-91 yr). Average time between first symptoms of the disease and diagnosis was 3.6 months. At diagnosis, peripheral nodes were present in all but 1 patient, and were generalized in 90% of cases. Constitutional symptoms were reported in 77% of cases and spleen enlargement in 51%. A cutaneous eruption--morbilliform, urt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(46 citation statements)
references
References 53 publications
2
44
0
Order By: Relevance
“…2 It is clinically characterized by widespread lymphadenopathy, and commonly, extranodal disease, immune-mediated hemolysis, and polyclonal hypergammaglobulinemia. 3 The recent identification of the follicular helper T cell (TFH) as the cell of origin of this lymphoma 4,5 represents a major step in the understanding of the clinicobiological characteristics of the disease. 6 This T-cell subset promotes positive selection, proliferation and differentiation of germinal center antigen-specific B cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is clinically characterized by widespread lymphadenopathy, and commonly, extranodal disease, immune-mediated hemolysis, and polyclonal hypergammaglobulinemia. 3 The recent identification of the follicular helper T cell (TFH) as the cell of origin of this lymphoma 4,5 represents a major step in the understanding of the clinicobiological characteristics of the disease. 6 This T-cell subset promotes positive selection, proliferation and differentiation of germinal center antigen-specific B cells.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cases of AITL are associated with EBV, which can be detected with the use of in-situ hybridization studies (EBER) or immunohistochemistry 7,9,22–24 . Biologically, EBV enters the B-cells and CD21 positive follicular dendritic cells (FDC) and immortalizes them 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Later, Watanabe et al 6 hypothesized that AITL was a proliferation of hyperactive B-cells. We now know that AITL is the second most common type of peripheral T-cell lymphoma (PTCL) worldwide, and in some countries the most common form 1,79 . Clinically, AITL usually presents with a constellation of findings that include diffuse lymphadenopathy, hepatosplenomegaly and constitutional symptoms (fever, chills, weight loss, etc).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 77 patients, Lachenal et al [27 ]reported neurologic symptoms, including confusion, loss of hearing or vision, motor and sensory polyneuritis and aphasia, in 8 patients (10%). In 2 of these patients, tumor cells were identified in the CSF and lymphocytic meningoencephalitis was present in 1 patient.…”
Section: Discussionmentioning
confidence: 99%